Pengaruh Pengungkapan Sustainability Report Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Moderating (Studi Empiris pada Perusahaan Pertambangan Yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023) - Lasuardhi, Dony; Jacobus Widiatmoko; Muhammad Ali Ma'sum (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
This research aims to empirically test the effect of sustainability report disclosure on company value with profitability as a moderating variable (Empirical Study of Mining Companies Listed on the Indonesia Stock Exchange 2019-2023). The population of this research is all mining companies listed on the Indonesia Stock Exchange for 2019-2023, totaling 63 companies. The sample used in this research was 12 companies. This research uses a purposive sampling technique, namely a sampling technique that provides the opportunity to become a sample member with certain criteria. Then the data collection method is through questionnaires and data analysis using SPSS 25 which includes validity, reliability, classical assumption tests, multiple regression analysis, hypothesis testing using the t test and R2 test. The results of this research show that the Sustainability report variable has a positive effect on the value of mining companies listed on the Indonesia Stock Exchange in 2019-2023, so (H1) is accepted. The Profitability variable has no effect on the Company Value of mining companies listed on the Indonesia Stock Exchange in 2019-2023, so (H2) is rejected. The profitability variable is not able to moderate the relationship between sustainability reports and company value.